2020
DOI: 10.35188/unu-wider/2020/871-9
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and assortative matching of partners in international trade

Abstract: This study has been prepared within the UNU-WIDER project How do effective states emerge?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(99 reference statements)
1
0
0
Order By: Relevance
“…Finally, it is revealed that tariff rate and non-tariff barriers, which are dimensions of Trade Freedom, and restrictions on investments, payments, transfers, and capital transactions, which are dimensions of Investment Freedom, have a significant impact on the corruption in this study. The significant impact of Trade Freedom and Investment Freedom on Corruption is frequently emphasized in the literature (Shirazi, 2020;Cooray et al, 2020;Smidova, 2020;Qureshi et al, 2020;Zheng & Xiao, 2020). Similar to the studies in the literature, a positive correlation between Trade Freedom, Investment Freedom, and Corruption is revealed in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, it is revealed that tariff rate and non-tariff barriers, which are dimensions of Trade Freedom, and restrictions on investments, payments, transfers, and capital transactions, which are dimensions of Investment Freedom, have a significant impact on the corruption in this study. The significant impact of Trade Freedom and Investment Freedom on Corruption is frequently emphasized in the literature (Shirazi, 2020;Cooray et al, 2020;Smidova, 2020;Qureshi et al, 2020;Zheng & Xiao, 2020). Similar to the studies in the literature, a positive correlation between Trade Freedom, Investment Freedom, and Corruption is revealed in this study.…”
Section: Discussionsupporting
confidence: 87%